The Challenges of Providing Diabetes Education in Resource-Limited Settings to Women With Diabetes in Pregnancy: Perspectives of an Educator - Goldschmidt, Virginia J. (Diabetes Spectr, 2016)
IN BRIEF In resource-limited settings, the challenges of providing diabetes education are magnified. To provide the best education, these challenges and barriers need to be identified and addressed. Many times, at the “teachable moment” of a gestational diabetes diagnosis, we are able to not only address the immediate concerns, but also help patients adopt and continue long-term healthy lifestyle behaviors that improve the health of their entire family.